Cone-beam computed tomographic evaluation of root canal morphology of mandibular anterior teeth in a Saudi subpopulation, retrospective In-Vivo study - Muath Alshayban; Turki Abughosh; Waleed Almalki; Mishary Alrasheed (Saudi Dental Journal)
Background: There is variability in the results of dental morphological studies between different ethnic populations. This study aimed to investigate the root canal morphology of mandibular anterior teeth in a Saudi subpopulation in the Riyadh region. Methods: We examined a total of 1,769 cone-beam computed tomography (CBCT) images of the mandibular anterior teeth, including the central incisors (n = 587), lateral incisors (n = 590), and canines (n = 592). The number and configuration of the root canals were determined. Fisher's exact and Pearson’s chi-square tests were used to assess the differences between sexes and age groups, with a level of statistical significance was set at p < 0.05. Results: Overall, Type I canal was the most frequent configuration among the mandibular anterior teeth (76.1%). However, the prevalence of Type III canal configuration in the central and lateral incisors was 36.5% and 31%, respectively. Additionally, the mandibular canines were mainly Type I canals (98.4%). The prevalence of canal configuration was predominantly Type I (95.7%), followed by Type III (2.7%), Type IV (0.4%), and Type V (1.2%). There was a statistically significant difference in the canal configurations between men and women (p = 0.02). Females more often had Type I root canals (60.6%), while Type III was more frequent in males (57.2%). However, there were no statistically significant differences between the age groups in canal configuration. Conclusion: The mandibular anterior teeth of the Saudi subpopulation had mainly one root canal. However, almost one-third of the central and lateral incisors had two canals. CBCT is a useful tool that can be used, if available, to investigate root canal morphology before root canal treatment.